Potentials of top management team career development and corporate social responsibility: A study on listed manufacturing companies in China. Issue 6 (30th July 2019) - Hu, Yelin; Zhang, Qiwang; Wang, Xin
Abstract : Purpose: The purpose of this paper is to explore the relationship between potentials of top management teams' (TMT) career development and corporate social responsibility (CSR) by examining listed manufacturing companies in China. More importantly, it tried to contribute to the understanding of the senior executive's career development in the trend of upgrading the manufacturing industry. Design/methodology/approach: The sample firms in this paper were selected from the China A-listed companies in the manufacturing industry. It collected CSR and TMT data from the Rankins CSR Ratings (RKS) Database and CSMAR database and applied the multiple regression to test the hypotheses. Moreover, it implemented the robustness test by using the standard regression method and the structural equation model. Findings: The findings indicate that a firm's CSR performance is significantly associated with TMT's educational level and overseas background. The government background, academic background and financial background of high-level managers, instead, have a negative relationship with CSR performance. In addition, firm's ownership moderates the relationship between TMT and CSR initiatives – the career development potential of TMT has different effects on promoting CSR in the context of different ownership. These relationships remain significant when the managers' tenure, gender, age, wage and firm size are controlled. Research limitations/implications: The empirical research on the potentials of executive career development and CSR is limited to linear assumptions. Since there are fewer overseas holding companies in Chinese state-owned and private enterprises, it failed to reflect international differences. Practical implications: First, CSR is related to the potentials of TMT career development and also the potentials of TMT career development are associated with the structure of the TMT. Second, to improve CSR, it is necessary to distinguish the different ownership of companies and then adjust the TMT structure correspondingly. Last, senior executives should choose their career direction according to their own distinct and inherent career development potentials. Originality/value: This study explores the relationship between potentials of TMT career development and CSR. It not only expands the research in the field of CSR but also enriches the research on the career development of top executives.